Bioestimulant with Ascophyllum nodosum and fulvic acids as mitigating factors of salinity damage in soybean - Bruna A. da Silva; Johny de S. Silva; Toshik I. da Silva; Rafael S. da Costa; Carolina S. de Castro; Letícia K. B. de Oliveira; Tomil R. M. de Sousa; Carlos Y. A. C. Rodrigues; Flávio B. Cardoso; Rosilene O. Mesquita (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Soil salinization negatively affects the growth and yield of economically valuable crops such as soybeans. New technologies are being developed to minimize the damage caused by saline stress and improve crop performance. Therefore, the use of biostimulants in agriculture may offer an alternative method to mitigate the deleterious effects of salinity. Extracts of the seaweed, Ascophyllum nodosum and humic substances (fulvic acids) are commonly used. Therefore, this study aimed to evaluate the action of a biostimulant composed of A. nodosum seaweed extract and fulvic acid applied at different phenological stages on the biometric, biochemical, and physiological parameters of soybeans (Glycine max) subjected to irrigation with saline water. The experimental design used was completely randomized in a 3 × 2 + 2 factorial scheme, referring to three applications of the biostimulant at different soybean phenological stages: V3, V3R1, and V3R1R4, two levels of electrical conductivity of irrigation water (ECw): 0.5 (S0) and 5.0 dS m-1 (S1), two additional controls, one with a positive control (PC) and the other with a negative control (NC). The experiment had five replicates with one plant per plot. The results of this study suggest that the application of the biostimulant can mitigate the harmful effects of salt stress in soybeans. The results obtained with V3R1 application in the parameters stem diameter, leaf area, shoot dry mass, electrolyte leakage, and chlorophyll b represent greater efficiency in mitigating the harmful effects of salinity in soybean cultivation.